Pengaruh Transformasi Digital Terhadap Kinerja Keuangan Melalui Efisiensi Operasional Pada Perbankan Periode 2015-2024 - Quinasa Rama Herlanlam; Gatot Nazir Ahmad; Ryna Parlyna (INDO PUBLISHING, 2026)
This study aims to analyze the effect of digital transformation on financial performance, with operational efficiency as a mediating variable, in the Indonesian banking sector. The background of this study is based on the massive adoption of digital technology in the banking industry, which requires significant capital investment, potentially having a dual impact in the form of increased revenue and pressure on banks' operating expenses. This study uses a quantitative approach with a panel data regression method to estimate the relationship between variables. The study population includes commercial banks listed on the Indonesia Stock Exchange, with samples drawn using a purposive sampling technique during the 2015–2024 period, resulting in data from 25 banks that meet the criteria. The analysis technique involves selecting the best model through the Chow and Hausman test, the classical assumption test, and the Sobel test for mediation. The results show that digital transformation has a positive effect on operating expenses and also has a significant positive and direct effect on financial performance. Operational efficiency has been shown to have a significant negative effect on financial performance. Furthermore, operational efficiency plays a significant role as a mediating variable in the relationship between digital transformation and financial performance, with a negative indirect effect. These findings confirm that while digital transformation is a strategic asset capable of boosting revenue according to the Resource-Based View theory, its success in increasing profitability depends heavily on management's ability to efficiently control investment costs.